Comparative morphology of spermatozoa and reproductive systems of zorapteran species from different world regions (Insecta, Zoraptera) - Dallai, Romano; Gottardo, Marco; Mercati, David; Machida, Ryuichiro; Mashimo, Yuta; Matsumura, Yoko; Rafael, José Albertino; Beutel, Rolf Georg (Arthropod Structure and Development, 2014)
The male and female reproductive apparatus of Zorotypus magnicaudelli (Malaysia), Zorotypus huxleyi (Ecuador) and Zorotypus weidneri (Brazil) were examined and documented in detail. The genital apparatus and sperm of the three species show only minor differences. The testes are larger in Z. magnicaudelli. Z. huxleyi lacks the helical appendage in the accessory glands. A long cuticular flagellum is present in Z. magnicaudelli and in the previously studied Zorotypus caudelli like in several other species, whereas it is absent in Z. weidneri, Z. huxleyi, Zorotypus hubbardi, Zorotypus impolitus and Zorotypus guineensis. Characteristic features of the very similar sperm are the presence of: a) two dense arches above the axoneme; b) a 9+9+2 axoneme with detached subtubules A and B of doublets 1 and 6; c) the axonemal end degenerating with enlarging accessory tubules; d) accessory tubules with 17 protofilaments; e) three accessory bodies beneath the axoneme; and f) two mitochondrial derivatives of equal shape. The first characteristic (a) is unknown outside of Zoraptera and possibly autapomorphic. The sperm structure differs distinctly in Z. impolitus and Z. hubbardi, which produce giant sperm and possess a huge spermatheca. The presence of the same sperm type in species either provided with a sclerotized coiled flagellum in males or lacking this structure indicates that a different organization of the genital apparatus does not necessarily affect the sperm structure. The flagellum and its pouch has probably evolved within Zoraptera, but it cannot be excluded that it is a groundplan feature and was reduced several times. The fossil evidence and our findings suggest that distinct modifications in the genital apparatus occurred before the fragmentation of the Gondwanan landmass in the middle Cretaceous. © 2014 Elsevier Ltd.
Keywords: Animals Experiment; Animals Tissue; Axoneme; Comparative Anatomy; Female; Genital System; Male; Nonhuman; Spermatheca; Spermatozoon; Ultrastructure; Zoraptera; Zorotypus Caudelli; Zorotypus Guineensis; Zorotypus Hubbardi; Zorotypus Huxleyi; Zorotypus Impolitus; Zorotypus Magnicaudelli; Zorotypus Weidneri; Africa; Anatomy And Histology; Animals; Cytology; Evolution; Female Genital System; Insect; Malaysia; Male Genital System; South America; Species Difference; Spermatozoon; Hexapoda; Insecta; Zoraptera; Zorotypus; Zorotypus Hubbardi; Africa; Animal; Biological Evolution; Female; Genitalia, Female; Genitalia, Male; Insects; Malaysia; Male; South America; Species Specificity; Spermatozoa